PENGENALAN SISTEM INFORMASI AKUNTANSI DI DUNIA KERJA: OUTSOURCING SYSTEM OF ENTERPRISE BUSINESS PROCESS - Made Irma Lestari (Jurnal Abdi Mandala, 2022)
Accounting Information System (AIS) as an information provider machine, the intelligence of the business language, owned by the company will always change and is needed to change due to various factors, one of which is changes in business processes. Companies are faced with the decision to provide the need for an effective and efficient AIS. Companies can have one of three ways to acquire an AIS, including purchasing software, developing their own software in-house, or using AIS services and products from a system vendor (outsourcing). This community service was packaged in the form of an online public lecture which was attended by around 35 people consisting of college students in STIE Wiyatamandala and the general public. It is hoped that on the next occasion, public lectures or similar events with the topic of in-house system development can be held.